PINTO BRAVO: A NEW DRY BEAN VARIETY FOR THE SEMIARID MEXICAN HIGHLANDS - Rosales Serna, Rigoberto; Acosta Gallegos, Jorge Alberto; Ibarra Pérez, Francisco Javier; Cuéllar Robles, Evenor Idilio (Revista Mexicana de Ciencias Agrícolas, 2018)
In the Semiarid Highlands of Mexico, the pinto bean is one of the main commercial classes produced under rainfed conditions. It’s required grain-tolerant varieties of the seed coat darkening, early maturity and larger seeds in relation to Pinto Saltillo’s, which is the most popular variety in the region. The objective was to develop a superior bean variety than Pinto Saltillo in earliness, grain size and commercial quality. The staff of the National Research Institute for Forestry, Agriculture and Livestock generated in Durango, the Pinto Bravo variety, using the genealogical method from the cross between Pinto Mestizo and Pinto Saltillo [(Pinto Mestizo/Pinto Saltillo)-7-4]. This variety showed an average yield of 1 178 kg ha-1 and a fluctuation between 329 kg ha-1 and 3 045 kg ha-1. On average, Pinto Bravo compared with Pinto Saltillo, had more precocious maturity (88 vs 93 days) and had greater weight of 100 seeds (36 g vs 31 g). The growth habit of Pinto Bravo is indeterminate vine, with short no- climbing guides, canopy average height of 27 cm and 75 cm guide. Pinto Bravo has an average weight of 36 g/100 seeds and variations between 25 and 46 g per 100 seeds. The grain shape is transversally elliptic and elliptical rhomboid in the external view. The head is creamy color, light brown speckles and yellow hilum. Pinto Bravo has tolerance to anthracnose and rust; as well as medium and high values of susceptibility to common blight and root rots. This variety is currently being validated on producers land and seeds will be reproduced to establish their suitability and potential, in order to increase the commercial quality of beans produced in the semi-arid highlands of Mexico.
Keywords: Phaseolus vulgaris L.; commercial quality; improved variety; yield